Institutional Importance in the Indonesian Rigidity System - Madon Yanuar (Fakultas Hukum Universitas Lampung, 2020)
The formation of special institutions regulated by law has the same status as those regulated in constitution (constitutional importance). The purpose of this paper is to determine the urgency of the existence of a special state institution that has a constitutional importance in Indonesia's strictness system, in this case the state institutions are the National Human Rights Commission and the KPK. The writing method used is to use normative legal research. The results of the discussion illustrate that the emergence of a new state institution that is regulated by law, namely as a functional institution that handles a problem within their respective scope. The conclusion is that to overcome the complexity of problems that arise in society. The recommendation in this writing seeks to ensure that institutions which have the same degree as existing institutions are constituted to be included in the constitution in order to strengthen their position and authority.